Teoria do farol : fundamentação para a prática de enfermagem na promoção da saúde de homens - Rosa, Isabele Torquato Mozer (2024)
The objective was to devise a medium-range theory for enhancing the well-being of men, derived from Nola Pender's conceptual framework. According to Fawcett, Nola Pender's theoretical model for health promotion was initially analyzed. The main idea of the theory, promoting men's health, was defined using a technique called concept analysis. We used data from a study done in many different parts of Brazil between 2018 and 2021 to organize the data. The outcomes were categorized into three distinct chapters. The initial chapter presents Nola Penders Health Promotion Model without any reliance on value judgments or third-party interpretations. In addition to getting closer to the theoretical precepts and understanding the origins, it allows to produce a theoretical guide to be used in various ways. The second chapter presents the concept of Men's Health Promotion. It is defined as seeking out health services and health professionals to obtain help to improve their wellbeing, prevent illnesses and diseases, and take/maintain actions aimed at self-care. These actions involve: proper nutrition, regular physical activity, hydration, hygiene and rest, environmental forecasts, practices linked to culture and religiosity, aesthetic care and physical appearance, low alcohol intake, no smoking, safe sexual practices, up-to-date vaccination schedule, attentive attention to mental health aspects and leisure time. The antecedents, consequents, model cases, contrary, borderline, and concept-related cases were also presented. The third chapter describes the Lighthouse Theory, consisting of its purpose, context, central concept, five key concepts related to the nursing metaparadigm, 11 assumptions, and graphic modeling. To facilitate nursing professionals in incorporating the Lighthouse Theory into their practice, guidelines for practice were devised, which encompassed the correlation of the Theory with the phases of the nursing process, as per the current legislation. It is hoped that this theory can contribute to demonstrating the importance of the male population in gender equality, as well as raising the profile of professional nurses when it comes to promoting men's health. Thus, this study confirmed the thesis that a nursing TMA to improve men's health promotion should consider aspects related to masculinities and the motivations that make men engage in behaviors aimed at improving their health.